Efektivitas Pembelajaran Dengan Metode E-Learning Pada Mahasiswa Keperawatan - Ria Efkelin; Hardin La Ramba; Ni Made Suarti; Martini Martini; Ary Rahmaningsih; Lipin Lipin; Nia Rosliany; Dameria Br Saragih; Apriliana Pipin; Ernawati Ernawati (An-Najat, 2023)
The development of information and communication technology (ICT) can now be used as a support in the teaching and learning process in the world of higher education, especially in nursing education. This study examines the effectiveness of learning with e-learning methods in nursing students. The method used in this literature view is based on 7 articles ranging from 2019 – 2023 with online databases used are PubMed, Scopus, Proquest, SAGE, CINAHL, and Google Scholar. The keywords used in article searches are e-learning and student and nursing. Nursing education supported by technology is essential to develop clinical reasoning and communication skills in health professionals, especially nursing.